2005
DOI: 10.1111/j.1442-200x.2005.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Is leptin a predictive factor in the end of therapy response in chronic hepatitis B?

Abstract: Although the higher leptin value observed in children with ETR was not statistically significant, because of close interactions between leptin, cytokines and lymphocytes, it is thought that leptin should be investigated as a predictive factor of ETR in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…With regard to CHB patients, our data are consistent to those by Selimoglu et al [40] reporting higher leptin levels in children with CHB. Testa et al [15] have found lower leptin levels compared to controls, but their cohort of CHB patients was rather small and limited to non-cirrhotic.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to CHB patients, our data are consistent to those by Selimoglu et al [40] reporting higher leptin levels in children with CHB. Testa et al [15] have found lower leptin levels compared to controls, but their cohort of CHB patients was rather small and limited to non-cirrhotic.…”
Section: Discussionsupporting
confidence: 92%
“…Serum ferritin levels were indicated to be helpful in monitoring and predicting patients' responses to lamivudine therapy [27]. With respect to the stimulating role of leptin in T-cell immunity, determination of the leptin levels in children with chronic HBV infection showed that higher leptin value was observed in children with end of therapy response, but it was not statistically significant [28]. In the present study, we analyzed the changes of serum laminin levels during lamivudine treatment and their associations with treatment response regarding the role of laminin in not only liver fibrosis but also immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, role of circulating leptin has been documented in children with immune thrombocytopenic purpura (16,17), celiac disease (18), cystic fibrosis (19) and chronic liver diseases (20)(21)(22)(23). However, the role of leptin and bone metabolism in BA patients has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%